Crop residue allocation to livestock feed, soil improvement and other uses along a productivity gradient in Eastern Africa - Duncan, Alan J.; Bachewe, Fantu Nisrane; Mekonnen, Kindu; Valbuena, Diego; Rachier, Gideon O.; Lule, D.; Bahta, Mesfin; Erenstein, Olaf (Elsevier, 2016)
Crop residues are a key livelihood resource in smallholder mixed crop-livestock systems in Sub-Saharan Africa. With expansion of arable land and resultant decline in grazing resources, crop residues are becoming an increasingly important component of livestock feeds. This demand for livestock feeds has implications for the long-term sustainability of such systems since failure to return biomass to soils has implications for soil quality and the capacity of soils to support long-term productivity. Biomass allocation patterns are likely to vary with overall level of productivity and hence availability. In this study we used a household survey to quantify crop residue allocation patterns across a gradient of productivity in Eastern Africa focusing on two sites in Ethiopia and one in Kenya. We assessed the underlying determinants of crop residue allocation patterns with a view to understanding how productivity increases through intensification will influence biomass allocation in Eastern Africa and how livelihood and natural resource management objectives could be optimized. Results showed that farmers strongly favour allocation of residues to livestock feeding but that allocation to soil increases along the productivity gradient. This reduced feeding to livestock and increased allocation to soil fertility is associated with smaller farm sizes leading to reduced animal traction needs for tillage, increased overall livestock productivity, increased use of inputs and a reduced reliance on farm-based activities in overall livelihood strategies. The implications of these trends are that productivity increases in smallholder systems are likely to reduce pressure on biomass in the long term and that measures that enhance the prospects for farmers to intensify their production systems are likely to increase soil health and sustainability objectives in general. A key conclusion of the work is that intensification of livestock production could reduce crop residue allocation to soils with long term implications for soil productivity.